The Effect of Visitor Export, International Tourist Arrival, Foreign Direct Investment, and Labor on Economic Growth in ASEAN in 2010-2022 - Sylviana, Widya; Dewi, Ardhani Nastiti (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2024)
This study seeks to investigate the impact of tourism factors on economic growth, specifically international tourist arrivals (ITA), visitor exports, foreign direct investment (FDI), labor, and COVID-19 as a dummy variable in ASEAN from 2010 to 2022, both partially and simultaneously. The dependent variable in this study is the Gross Domestic Product (GDP) value. The independent variables are international tourist arrivals (ITA), visitor exports, FDI, labor, and COVID-19 as dummy variables. This study utilized dynamic panel data regression using the Generalized Method of Moments (GMM). The selected model is the System Generalized Method of Moments (SYS-GMM). The findings of this study demonstrate that all independent variables collectively exert a significant influence on economic growth across the 10 ASEAN nations. In contrast, foreign direct investment and labor considerably impact economic growth in ten ASEAN nations. In contrast, partially, international tourist arrivals, visitor exports, and the COVID-19 dummy variable have no influence.